Natural fractures at depth in the Lower Cretaceous Kuqa Depression tight sandstones: identification and characteristics. (13th August 2020) - Nian, Tao; Li, Yanze; Hou, Tao; Tan, Chengqian; Liu, Chao
Abstract: The Kuqa Depression in the northern Tarim Basin, NW China, is characterized by fault-controlled anticlines where natural fractures may influence production. Natural fractures in the Lower Cretaceous tight sandstones in the depression have been studied using seismic profiles, borehole images, cores and thin-sections. Results show that thrust faults, two types of opening-mode macrofractures and two types of microfractures are present. Thrust faults were generated during Cenozoic N–S-directed tectonic shortening and have hydraulically linked Jurassic source rocks and Cretaceous sandstones. Opening-mode fractures can be subdivided on the basis of sizes, filling characteristics and distribution patterns. Type 1 macrofractures are barren or mainly calcite-lined. They have straight traces with widths (opening displacements) that are of the order of magnitude of 10 μm, suggesting that their primary role is that of migration channels. Type 2 macrofractures are calcite-filled opening-mode fractures. They have an elliptical or tabular shape with sharply tapering tips. Transgranular microfractures are lens-shaped and open or filled mostly by calcite; maximum widths range between 0.01 mm and 0.1 mm. Intragranular microfractures are the most common microfracture type. They are filled by calcite, feldspar or quartz. The macrofractures and transgranular microfractures have regular distributions, while most intragranular microfractures are irregularly distributed owing to their inherited origin. The results imply that natural fractures in the tight sandstones were formed as tectonic, diagenetic and natural hydraulic origins. In situ stress and cementation analyses suggest that Type 1 macrofractures and their genesis-related microfractures have controlled the present flow system of the tight sandstones.